TRANSVERSE LAPAROTOMY DURING COLON OPERATIONS - Лещишин, Ярослав Миронович; Савостьянов, Илья Васильевич; Данильченко, Иван Юрьевич; Развозжаев, Юрий Борисович; Мутагасимов, Игорь Григорьевич (Medicine in Kuzbass, 2019)
Anatomical and physiological characteristics indicate the advantages of transverse laparotomy in comparison with the median access, but the spatial characteristics of these approaches were practically not subjected to comparative evaluation. Aim – to determine the parameters of transverse laparotomy during operations on the colon in an anatomical study. To compare the parameters of median and transverse laparotomy during operations on the colon in anatomical study and according to spiral computed tomography. To evaluate the immediate results of the use of transverse laparotomy in operations on the colon. Materials and methods. In the anatomical study, measurements were carried out on the corpses of the male field, normosthenic physique upper - transverse laparotomy was performed in 25 cases, median – in 14. At the same time, an X-RAY examination with the analysis of 51 SCT studies was carried out. The clinic performed 18 surgical interventions for the pathology of the colon using upper-transverse laparotomy. Results and conclusion. Upper-transverse laparotomy has acceptable spatial characteristics during operations on the upper floor of the abdominal cavity, both in absolute values of angular characteristics and in relative point terms. The differences in the measurement data of x-ray and anatomical studies are due to the peculiarities of the techniques, as well as pre-accepted unchangeable access conditions (width). Clinical use of upper-transverse access in colon surgery was not accompanied by specific complications, as well as insurmountable technical difficulties associated with access, which can be regarded as an argument for its wider use in practical surgical activities.